Pengaruh Content Marketing, FOMO, dan Religious Commitment Terhadap Keputusan Pembelian Produk Halal: Pada Tiktok Shop di Kalangan Muslim Gen Z - Ika Choilia Indrianti; Fitriah Dwi Susilowati (Jurnal Ekonomika dan Bisnis Islam, 2026)
The development of digital media has encouraged the use of Content Marketing as a marketing strategy that may influence consumers’ psychological conditions, including Fear of Missing Out (FoMO), particularly among Generation Z who are highly active on social media. This study aims to examine the effect of Content Marketing on Fear of Missing Out (FoMO) and its implications for purchase decisions among Muslim Generation Z in Surabaya. A quantitative approach was employed using a survey method through questionnaire distribution to Muslim Generation Z respondents in Surabaya. The results show that Content Marketing affects Fear of Missing Out (FoMO), while FoMO does not affect purchase decisions. The findings contribute to consumer behavior studies based on the Stimulus Organism Response (S-O-R) theory and provide practical insights for businesses in developing informative and ethical Content Marketing strategies